O podstawowym - i niepodstawowych sposobach istnienia - Krajewski, Władysław (Filozofia Nauki, 2002)
There is one fundamental and many non-fundamental kinds of existence. Things (material bodies) exist fundamentally. Many other objects exist non-fundamentally: properties, events, relations, states; abstracts (universals), laws of Nature; possible states, virtual particles; minds, mental processes; ideal objects created by minds (Popperian "World 3"). All of them are always based on material bodies, but they exist really.